2014
DOI: 10.1039/c4ra00974f
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effect on the ground state proton transfer in the H-bonded HBDI complex: an implication of the green fluorescent protein

Abstract: In this paper, first-principles calculations were performed regarding the electric field effect on the ground state proton transfer (GSPT) in the H-bonded p-hydroxybenzylideneimidazolidinone (HBDI) network that represents the active site of the green fluorescent protein (GFP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Meanwhile, R C2–C3 and R C3–C4 are 1.404 and 1.390 Å, due to the bonding character (π) of both C2–C3 and C3–C4, as seen from the HOMO. This phenomenon is similar to that in the cis isomers …”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Meanwhile, R C2–C3 and R C3–C4 are 1.404 and 1.390 Å, due to the bonding character (π) of both C2–C3 and C3–C4, as seen from the HOMO. This phenomenon is similar to that in the cis isomers …”
Section: Resultssupporting
confidence: 83%
“…The magnitude of equilibrium constant was found to be closely fitted to a linear relationship under the effect of electric fields. The electric field was further revealed to significantly alter the GSPT mechanism, which is concerted and asynchronous in field‐free conditions . Additionally, it was found that the electric field parallel to a specific orientation can significantly affect the photochemical properties .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Theoretical and experimental studies have examined the influence of electric fields and electrostatics on radiative and nonradiative rates. ,,,, For example, TD-DFT calculations on the isolated GFP chromophore (Figure ) predict that electric fields can change the oscillator strength of an electronic transition and therefore the radiative rate constant. , Park and Rhee performed nonadiabatic molecular dynamics simulations on the GFP chromophore and found that electrostatic effects can outweigh steric factors impeding the twisting of the methine bridge between the phenoxy and imidazolinone rings, suppressing a major pathway for nonradiative relaxation . Drobizhev and co-workers investigated these issues by measuring two-photon absorption cross sections of RFPs .…”
Section: Brightnessmentioning
confidence: 99%